Decision making in euthymic bipolar I and bipolar II disorders - Martino, Diego Javier (2010)
Background. The main aim of this study was to compare a large population of patients with bipolar disorder (BD) types I and II strictly deﬁned as euthymic with healthy controls on measures of decision making. An additional aim was to compare performance on a decision-making task between patients with and without a history of suicideattempt.Method. Eighty-ﬁve euthymic patients with BD-I or BD-II and 34 healthy controls were included. All subjects completed tests to assess verbal memory, attention and executive functions, and a decision-making paradigm (the Iowa Gambling Task, IGT).Results. Both groups of patients had worse performance than healthy controls on measures of verbal memory, attention and executive function. No signiﬁcant diﬀerences were found between BD-I, BD-II and healthy controls on measures of decision making. By contrast, patients with a history of suicide attempt had lower performance in the IGT than patients without a history of suicide attempt.Conclusions. Patients with euthymic BD-I and BD-II had intact decision-making abilities, suggesting that this does not represent a reliable trait marker of the disorder. In addition, our results provide further evidence of an association between impairments in decision making and vulnerability to suicidal behavior.